EL CUERPO ORGANIZADO: SOCIOPOLÍTICA DE LAS REPRESENTACIONES ANTROPOMORFAS EN LA CERÁMICA PREHISPÁNICA DE VENEZUELA - Escalona Villalonga, Carlos (2010)
In Venezuela there has been little systematic research has focused entirely on the pre-Columbian pottery human figuration. They have worked on a regional problem limited to the Valencioid interaction sphere and the Andean area. Accordingly, by this work, using as a frame of reference the anthropomorphic figurative pieces egalitarian tribal societies Barrancoid-Saladoid in the Orinoco and tribal cultures and hierarchical cacicales Valencioid Mirinday Betijoque-central coast and in the Venezuelan Andes, respectively. We considered an inquiry by way of comparison between different periods, regions and / or culture from body theory in archeology. Through formal deconstruction of parts for the definition of figurative patterns, dare we say anthropomorphic ceramic pieces were probably powerful vehicles used by the company to spread personal and communal identities and reveal socially accepted power relations between the individuals and their environment.